Bamboo shoot : superfood for nutrition, health and medicine - Chongtham, Nirmala; Bisht, Madho Singh (Boca Raton, FL ; Abingdon, Oxon : CRC Press, 2021)
"Bamboo is an ordinary plant with extraordinary properties. Bamboo is an important resource for a healthy planet, and its shoots hold manifold nutritional benefits. Based on 18 years of research, Bamboo Shoot: Superfood for Nutrition, Health and Medicine details health-promoting bioactive compounds found in bamboo and offers practical guidance on how this vegetable, bamboo shoot, is used for food fortification. Bamboo shoots aid in the prevention of cardiovascular disease, cancer, diabetes, hypertension and obesity. Exploring the tradition and culture of bamboo in Asian countries, this book provides information on the science behind the nutritional value of bamboo shoots"--
OCLC-licensed vendor bibliographic record.
Keywords: Bamboo; Shoots (Botany); Nutrition; Phytochemicals; Functional foods; MEDICAL / Alternative Medicine; MEDICAL / Nutrition